KUALITAS SEMEN BEKU SAPI BALI PASCA THAWING DALAM WAKTU BERBEDA (Quality of Bali Bull Frozen Semen Post Thawing in Differents Times) - Fafandri .; Ni Luh Gde Sumardani; I Wayan Suberata (Universitas Nusa Cendana, 2023)
The aim of this research was to know quality of bali bull frozen semen post thawing in defferent times. The research was conducted in Livestock Reproduction Laboratory of the Faculty of Animal Husbandry, Udayana University, Bukit Jimbaran, bali Province in one months. The treatment of this research are T 1 (thawing in 15 seconds), T 2 (thawing in 30 seconds), and T3 (thawing in 60 seconds) on temperatur 37oC. The data of research was sperm motility, sperm viability, and sperm abnormality. Result of this research showed that the quality of bali bull frozen semen post thawing in defferent times that 15 second (T 1), 30 second (T 2), and 60 second (T 3) did not significantly (P> 0.05). The best thawing is at T3 treatment with sperm motility 71.00±2.00%, sperm viability 56.07±1.69%, and sperm abnormality 1.97±0.47%. The conclusion of this study is the bali bull frozen semen can be thawed at temperature 37oC in 60 seconds.